International Migration and Social Entrepreneurship: The Role of the Insan-Leilek Foundation in Supporting Migrants from Kyrgyzstan (Халықаралық қатынастар және халықаралық құқық сериясы, 2026)
The article analyzes the social challenges faced by labor migrants from Kyrgyzstan working in Russia, as well as by their families both in the country of origin and in the host society. It is noted that approximately one million Kyrgyz citizens are employed in Russia, highlighting the significant socio-economic importance of labor migration. Particular attention is given to the activities of the Insan-Leilek Foundation, which studies and addresses the consequences of labor migration.The paper examines how the organization employs social entrepreneurship mechanisms to address social issues, combining human rights advocacy, educational initiatives, and social support with the implementation of sustainable projects. In particular, it explores the establishment of kindergartens as social enterprises, the provision of legal assistance to migrants’ families, educational support for children in southern Kyrgyzstan, and assistance to women migrants through a crisis center in Moscow.The study applies a qualitative methodology based on the analysis of open sources and semi-structured interviews with the foundation’s staff. The findings demonstrate that the integration of social entrepreneurship into the activities of non-profit organizations can strengthen the sustainability of social initiatives and expand support mechanisms for migrant communities. The case of the Insan-Leilek Foundation illustrates how income-generating social projects can be reinvested to finance humanitarian programs and protect vulnerable groups.The central research question of the article is how social entrepreneurship addresses the social problems faced by labor migrants and their families in Kyrgyzstan and Russia. The theoretical framework draws on approaches from international migration studies and social entrepreneurship. The empirical basis of the study consists primarily of semi-structured interviews with the foundation’s staff and open-source data.Key words: International labor migration, Social Entrepreneurship, Kyrgyzstan, non-commercial organisation.